Criminal Punishment under Russian Law of a Person for Failure to Report - Alexander V. Ostroushko3, Liudmila A. Bukalerova1, Saule K. Amandykova2,; Mikhail A. Eliseev5, Olga V. Avakova4, (Opción, 2019)
The aim of the study is to investigate the criminal punishmentunder Russian law of a person for failure to report on the existence ofhis second citizenship via the main provisions of the Russian science ofcriminal, migration, and international law. As a result, the guilty personis aware of the social danger of failure to fulfill the obligation. Inconclusión, the crime provided by Article 330.2 of the Criminal Codeof the Russian Federation, is deemed completed at the time of expiry inthe period during which the person was obliged to file a correspondingnotification.